2020
DOI: 10.1620/tjem.252.73
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk Factors among Hospitalized COVID-19 Patients in a Major Referral Center in Iran

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic has killed many people worldwide since December 2019, and Iran has been among the most affected countries. In this retrospective study, we aimed to determine the prognostic factors associated with mortality in COVID-19 patients by analyzing 396 survived and 63 non-survived patients in Shahid Modarres Hospital, Tehran, Iran, from January 30 th until April 5 th , 2020. As the results, the BMI > 35 (p = 0.0003), lung cancer (p = 0.007), chronic kidney disease (p = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
143
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(153 citation statements)
references
References 45 publications
7
143
2
1
Order By: Relevance
“…27 28 Likewise, statins use has been found to be associated with a reduced risk of adverse outcomes in patients with COVID-19. [4][5][6][7][8][9] The data are, however, limited and contradictory with some studies reporting no difference while others showing adverse outcomes in statin users compared with non-users. [10][11][12][13] In the present meta-analysis, we found that statin use was associated with improved clinical outcomes in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 28 Likewise, statins use has been found to be associated with a reduced risk of adverse outcomes in patients with COVID-19. [4][5][6][7][8][9] The data are, however, limited and contradictory with some studies reporting no difference while others showing adverse outcomes in statin users compared with non-users. [10][11][12][13] In the present meta-analysis, we found that statin use was associated with improved clinical outcomes in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Multiple observational studies have shown that prior use of statins is associated with a reduced risk of adverse outcomes in patients with COVID-19. [4][5][6][7][8][9] On the contrary, other studies showed either no differences in outcomes [10][11][12] or even adverse outcomes in statin users. 13 There exist two metaanalyses in this regard; while one showed that statin use did not improve the in-hospital outcomes, 14 the other reported a 30% reduction in fatal or severe disease.…”
Section: Introductionmentioning
confidence: 92%
“…11 A recent study showed there was no difference of aspirin usage between the survival and non-survival of COVID-19 patients. 12 To our knowledge, no study reported the relationship between low-dose aspirin and COVID-19 patients with CAD. As an important drug for secondary prevention of coronary artery disease, it is important to explore the relationship between the baseline use of low-dose aspirin and the clinical prognosis of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 96%
“…Most studies in the Middle East region focused on risk factors of mortality [16,17,18,19] among COVID-19 patients and, to our knowledge, very little (including a few papers from subsequent parts of the Jaber Hospital cohort) has been published on factors associated with the risk of ICU admission. More globally, an international meta-analysis showed that higher mortality was strongly associated with increasing age, male gender and the presence of obesity, HT, DM, CVD, and cancer, and with some excess mortality associated with several other comorbidities [20].…”
Section: Results Derived From the Modelsmentioning
confidence: 99%